Mechanical performance and optimization of high-volume fly ash concrete containing plastic wastes and graphene nanoplatelets using response surface methodology. (15th November 2021) - Adamu, Musa; Trabanpruek, Pattanawit; Jongvivatsakul, Pitcha; Likitlersuang, Suched; Iwanami, Mitsuyasu
Highlights: GNP was used to enhance properties of HVFA concrete containing plastic waste (PW). GNP reduces the negative effects of PW and HVFA on the properties of concrete. Response Surface Methodology (RSM) was used to optimize experimental variables. Equations were developed based on RSM to predict mechanical properties of concrete. Abstract: Effect of plastic waste (PW) and graphene nanoplatelets (GNP) on properties of high-volume fly ash (HVFA) concrete was investigated. Response surface methodology has been used for designing experiment, modelling, and optimization. The variables were PW, HVFA, and GNP, and the responses were strengths and water absorption. PW and HVFA reduce the strengths and absorption while GNP enhances them. The proposed models developed were significant with high level of correlation. Optimized mix was achieved by substituting 15.3% of coarse aggregate using PW, 6.07% of cement using HVFA, and adding GNP at 0.22%, and was experimentally validated with error less than 5%.